Strengthening Transfer of Technology Among High Altitude Community of Ladakh - Dorjey Angchok and R. B. Srivastava, (Indian Journal of Extension Education, 2013)
Different socio-cultural environment requires different method of technological interventions, so is true of cold-arid highaltitude communities (HACs). In India, cold-arid HAC like Ladakh (J&K) and Lahoul Spiti (HP) has been neglected inthis respect because of their lack of representation at national level due to their meager proportion in terms of populationsize. Though there has been considerable interest shown by social scientists in understanding the socio-culturalenvironment prevailing in these parts of the world, but there has been lack of interest among researchers to understand andcontrive a model of technology intervention among such communities. This has resulted into the adoption of 'copy andpaste' model of technology intervention modalities, where models adopted for lowlanders were/are applied for HAC atvarious policy decision making platforms. Therefore an effort has been made through this paper to understand the variousfactors (both local and contextual) whose understanding would help extension workers and policy makers in increasingthe efficacy and rate of technology transfer among HAC. Emphasis has been given to understand the prevailing localinstitutions, local wisdom and resource management practices and how these understanding could be applied in variousextension activities for an effective technology transfer and intervention. The present study limit itself to Ladakh regiondue to accessibility constraints and the familiarity of the results.